ANALISIS KEMAMPUAN KONEKSI MATEMATIS PADA POKOK BAHASAN STATISTIKA BERBASIS LESSON STUDY FOR LEARNING COMMUNITY - Rahmanti, Suci Amalina; Hobri, H; Oktavianingtyas, Ervin (Kadikma, 2018)
Abstract. This research describes about mathematic connection ability in class IX B SMP Negeri 7 Jember subject discussion is statistic. Data collection methods which were used are test and interview. The research subjects consist of 3 students where one student has high mathematical connection ability, one student has medium mathematical connection ability, and one student has low mathematical connection ability. Students with high mathematical connections have three indicators of mathematical connection capability. Students with medium mathematical connections have two indicators of mathematical connection capability, and students with low mathematical connection ability do not have the 3 indicators of mathematical connection capability. Keywords: Mathematic connection ability, statistic, lesson study for learning community